Bobby and Jackie : a love story - Heymann, C. David (Clemens David), 1945-2012 (Atria Books, 2009)
An in-depth look at the much talked-about -- but never fully revealed -- relationship between Jackie Kennedy and Robert F. Kennedy that began as a result of their shared grief over the assassination of the president in 1963 and lasted until Bobby began his run for the Democratic presidential nomination in 1968.